Prioritization vs. congestion on platforms: evidence from Amazon's Twitch.tv. (RAND Journal of Economics (Wiley-Blackwell), 2022)
This article studies the efficient use of prioritizing certain content over others in Amazon's Twitch.tv, a live streaming service, taking into account the trade‐off between entry and congestion. I specify and estimate supply and demand models for live video, and a congestion model. Using technological shocks, I identify congestion costs for content providers and their consumers. Using shocks in prioritization, I identify its benefits. With estimated preferences and technological parameters, I construct counterfactuals. Without congestion, demand doubles. A supply‐side Pigouvian tax on traffic is preferred to a demand‐side one. Without prioritization, consumer welfare drops by 10%.